A Passionate Humanitarian, V.K.R.V. Rao - Rao, H L; Rao, V. K. R. V. 1908-1991 (Vijendra Kasturi Ranga Varadaraja); Rao, S. L. (New Delhi : Academic Foundation in association with Institute for Social and Economic Change, 2008)
Commemorative volume on Vijendra Kasturi Ranga Varadaraja Rao, 1908-1991, Indian economist; contributed articles chiefly on his life and contribution in the establishment of Institute for Social and Economic Change.
Keywords: Economists; Economic development; Social change